METHOD OF CHOOSING TERMINAL EQUIPMENT OF PASSIVE OPTICAL NETWORKS BASED ON FUZZY MULTI-CRITERIA DECISION MAKING - PIDCHENKO, SERGIY; KUCHERUK, OKSANA; PYVOVAR, OLEH; IVANOV, OLEKSII; HORIASCHENKO, KOSTYANTYN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Currently, optical communication is the dominant technology in cable channels of transport networks, working with powerful homogeneous digital data streams. In particular, the PON (Passive Optical Network) technology is developing dynamically. However, one of the problems holding back PON development is the cost of line and subscriber equipment (Optical line terminal and Optical Network Unit). An urgent task at the moment is the rational choice of equipment when designing optical networks. Most problems in the design of telecommunication networks can be modeled as a multi-criteria decision-making problem, where it is necessary to evaluate several criteria and choose the most acceptable solution option for design engineers according to their preferences and requirements. The article considers the process of selecting an optical line terminal (OLT), which is associated with the evaluation of possible options by a set of indicators. The purpose of the study: building a model of the optimal choice of optical linear terminals in conditions of unclear information. The ambiguity of human judgments when evaluating the importance of criteria (indicators) and evaluating alternatives based on the criteria creates certain problems for decision-makers. The use of fuzzy logic allows processing inaccurate and uncertain information, providing a more complete and accurate assessment of alternatives and evaluation of the importance of criteria. The article proposes the use of fuzzy multi-criteria decision-making methods (Fuzzy MCDM). The Fuzzy SWARA and Fuzzy TOPSIS methods allow you to present an assessment of criteria and alternatives in a descriptive (linguistic) form, which facilitates the decision-making process. In the course of the research, alternatives and criteria for their evaluation were determined, a survey of experts was conducted, evaluations of the degree of importance of criteria and evaluation of alternatives according to criteria were determined. Based on the Fuzzy SWARA and Fuzzy TOPSIS methods, a fuzzy model for selecting an optical line terminal is built. The ranking of the selected optical linear terminals was obtained and the best one was determined.